A REVIEW OF THE EFFECTS OF LOW ELEVATION ANGLES ON THE PROPAGATION FOR SATELLITE COMMUNICATION LINK - Muhammad, Nura Idris; Abdullahi, Muhammad Yahaya; Abu, Yusuf Sani (FUDMA Journal of Sciences, 2023)
The propagation phenomenon for satellite communication links is affected by the elevation angle of the satellite. Low elevation angles can cause signal attenuation due to increased atmospheric absorption, increased multipath fading, and rain attenuation. These effects can lead to decreased signal-to-noise ratio, reduced link availability, and degraded performance. This paper examines the effects of low elevation angle on the propagation phenomenon for satellite communication links. The paper begins by discussing the basics of satellite communication links, including the components of a link, the types of signals used, and the various propagation phenomena that can affect signal transmission. It then focuses on the effects of low elevation angle on signal propagation, including multipath fading, scintillation, and rain attenuation. The paper discusses how these effects can be mitigated through various techniques such as antenna design and signal processing. The results suggest that increasing the antenna gain and using higher frequency bands can help reduce the impact of low elevation angles on satellite communication links. Finally, it provides an overview of current research in this area and suggests potential future research directions.